Economic and epidemiological evaluation of interventions to reduce the burden of hepatitis C in Yunnan province, China. - Alastair Heffernan; Yanling Ma; Shevanthi Nayagam; Polin Chan; Zhongdan Chen; Graham S Cooke; Yan Guo; Chuntao Liu; Mark Thursz; Wanyue Zhang; Xiaobing Zhang; Xiujie Zhang; et al. (PLoS ONE)
Background The paradigm shift in hepatitis C virus (HCV) treatment options in the last five years has raised the prospect of eliminating the disease as a global health threat. This will require a step-change in the number being treated with the new direct-acting antivirals (DAAs). Given constrained budgets and competing priorities, policy makers need information on how to scale-up access to HCV treatment. To inform such decisions, we examined the cost effectiveness of screening and treatment interventions in Yunnan, China. Methods and findings We simulated the HCV epidemic using a previously published model of HCV transmission and disease progression, calibrated to Yunnan data, and implemented a range of treatment and screening interventions from 2019. We incorporated treatment, diagnosis, and medical costs (expressed in 2019 US Dollars, USD) to estimate the lifetime benefits and costs of interventions. Using this model, we asked: is introducing DAAs cost effective from a healthcare sector perspective; what is the optimal combination of screening interventions; and what is the societal return on investment of intervention? The incremental cost-effectiveness ratio (ICER) of switching to DAAs with a median cost of 7,400 USD (50,000 Chinese Yuan) per course is 500 USD/disability adjusted life year (DALY) averted; at a threshold of 50% of Yunnan gross domestic product (2,600 USD), switching to DAAs is cost effective 94% of the time. At this threshold, the optimal, cost-effective intervention comprises screening people who inject drugs, those in HIV care, men who have sex with men, and ensuring access to DAAs for all those newly diagnosed with HCV. For each USD invested in this intervention, there is an additional 0·80 USD (95% credible interval: 0·17-1·91) returned through reduced costs of disease or increased productivity. Returns on investment are lower (and potentially negative) if a sufficiently long-term horizon, encompassing the full stream of future benefits, is not adopted. The study had two key limitations: costing data were not always specific to Yunnan province but were taken from China-level studies; and modelled interventions may require more operational research to ensure they can be effectively and efficiently rolled-out to the entire province. Conclusions Introducing DAAs is cost effective, the optimal package of screening measures is focussed on higher risk groups, and there are likely to be positive returns from investing in such HCV interventions. Our analysis shows that targeted investment in HCV interventions will have net benefits to society; these benefits will only increase as DAA costs fall.